2017
DOI: 10.3390/fermentation3010004
|View full text |Cite
|
Sign up to set email alerts
|

Gravity-Driven Adaptive Evolution of an Industrial Brewer’s Yeast Strain towards a Snowflake Phenotype in a 3D-Printed Mini Tower Fermentor

Abstract: Abstract:We designed a mini tower fermentor that is suitable to perform adaptive laboratory evolution (ALE) with gravity imposed as selective pressure, and suitable to evolve a weak flocculating industrial brewers' strain towards a strain with a more extended aggregation phenotype. This phenotype is of particular interest in the brewing industry, since it simplifies yeast removal at the end of the fermentation, and many industrial strains are still not sufficiently flocculent. The flow of particles (yeast cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 57 publications
(45 reference statements)
1
8
0
Order By: Relevance
“…The three strains-BCD1, BCD2, and BCD3-were characterized with a low flocculation ability and were continuously cultivated with high-glucose medium for 45 days. Small clusters of cells were observed around day 15, corresponding to approximately 110 generations, which is comparable to other S. cerevisiae ALE experiments [27,38,39]. The yeast cell clusters were not disrupted by treatment by EDTA, which indicated that the cell-cell interactions are not based on flocculins.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…The three strains-BCD1, BCD2, and BCD3-were characterized with a low flocculation ability and were continuously cultivated with high-glucose medium for 45 days. Small clusters of cells were observed around day 15, corresponding to approximately 110 generations, which is comparable to other S. cerevisiae ALE experiments [27,38,39]. The yeast cell clusters were not disrupted by treatment by EDTA, which indicated that the cell-cell interactions are not based on flocculins.…”
Section: Discussionsupporting
confidence: 83%
“…The aggregates persisted for all three strains. This indicated that the clusters are not the result of flocculin interactions and are likely due to failure in separation of the mother and daughter cells, described previously as the "snowflake" phenotype [27,[34][35][36]. The evolved strains were subsequently cultivated in batch cultures and the aggregating phenotype was found to be stable.…”
Section: Adaptive Evolution In Ministatsmentioning
confidence: 71%
See 2 more Smart Citations
“…Conjaerts and Willaert [9] performed adaptive laboratory evolution with gravity imposed as selective pressure for evolving a weak flocculating industrial strain towards a more flocculent phenotype. They used 3D printing to construct a suitable mini tower fermenter.…”
mentioning
confidence: 99%